2022
DOI: 10.1007/s40262-022-01129-y
|View full text |Cite
|
Sign up to set email alerts
|

Filgotinib: A Clinical Pharmacology Review

Abstract: Filgotinib (GS-6034, formerly GLPG0634; Jyseleca ® ) is an oral, preferential Janus kinase (JAK)-1 inhibitor. Preferential inhibition of JAK1 modulates a subset of proinflammatory cytokines within the JAK–signal transducer and activator of transcription pathway, which differ from those inhibited by JAK2 or JAK3. Filgotinib is absorbed extensively and rapidly after oral dosing and is metabolized by carboxylesterase isoform 2 to form its primary active metabolite, GS-829845. The primary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Currently, there are mainly 13 approved JAKi (Figure 3D) in the market: Ruxolitinib (1), [86][87][88][89][90][91] Tofacitinib (2), [92][93][94][95][96][97] Oclacitinib (for dogs), [98][99][100] Delgocitinib (3), [101][102][103][104] Baricitinib (4), [105][106][107][108] Upadacitinib (5), [109][110][111][112][113] Fedratinib (6), [114][115][116][117][118][119] Filgotinib (7), 68,[120][121][122][123] Abrocitinib (8), [124][125][126][127] Deucravacitinib (9), [128][129][130][131] Ritlecitinib (10), [132]…”
Section: Jak Inhibitors (Jaki)mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are mainly 13 approved JAKi (Figure 3D) in the market: Ruxolitinib (1), [86][87][88][89][90][91] Tofacitinib (2), [92][93][94][95][96][97] Oclacitinib (for dogs), [98][99][100] Delgocitinib (3), [101][102][103][104] Baricitinib (4), [105][106][107][108] Upadacitinib (5), [109][110][111][112][113] Fedratinib (6), [114][115][116][117][118][119] Filgotinib (7), 68,[120][121][122][123] Abrocitinib (8), [124][125][126][127] Deucravacitinib (9), [128][129][130][131] Ritlecitinib (10), [132]…”
Section: Jak Inhibitors (Jaki)mentioning
confidence: 99%
“…Currently, there are mainly 13 approved JAKi (Figure 3D) in the market: Ruxolitinib ( 1 ), 86–91 Tofacitinib ( 2 ), 92–97 Oclacitinib (for dogs), 98–100 Delgocitinib ( 3 ), 101–104 Baricitinib ( 4 ), 105–108 Upadacitinib ( 5 ), 109–113 Fedratinib ( 6 ), 114–119 Filgotinib ( 7 ), 68,120–123 Abrocitinib ( 8 ), 124–127 Deucravacitinib ( 9 ), 128–131 Ritlecitinib ( 10 ), 132–137 Pacritinib ( 11 ) 138–140 and Momelotinib ( 12 ) 141–144 . These drugs are used to treat various conditions including myelofibrosis, bone marrow cancer, rheumatoid arthritis (RA) and psoriasis.…”
Section: Jak Inhibitors (Jaki)mentioning
confidence: 99%
“…62 Filgotinib is another selective JAK1 inhibitor, as it has more than fivefold greater affinity to JAK1 versus JAK2, JAK3 and Tyk2. 63…”
Section: Evidence From Non-ibd Imids Studiesmentioning
confidence: 99%
“…Filgotinib is another selective JAK1 inhibitor, as it has more than fivefold greater affinity to JAK1 versus JAK2, JAK3 and Tyk2 63 . Winthrop et al recently reported a pooled safety analysis of seven RCTs of filgotinib in rheumatoid arthritis development program, in which 3691 patients received filgotinib for 6080.7 patient‐years of exposure (median 1.6, maximum 5.6 years) 64 .…”
Section: Risk Of Mace With Smdsmentioning
confidence: 99%
“…Für die JAK-Inhibitoren sind kürzere Halbwertszeiten beschrieben: Upadacitinib ca. 16 h 15 , Filgotinib 27,3 h 16 und Tofacitinib 3 h 17 . Hier ist wie bei Steroiden, Ciclosporin, Methotrexat und Tacrolimus eine Wartezeit von ca.…”
Section: Chronisch Entzündliche Darmerkrankungenunclassified